Answer:
B. 1
Step-by-step explanation:
-2|3x − 1| = 0
Divide by -2
|3x − 1| = 0
There is only one solution since 3x-1 must equal 0
3x = 1
x = 1/3
The correct answer is: [A]: " Look at the graph of the relationship. Find the y-value of the point that corresponds to x = 1 . That value is the unit rate."
<h3>What is y-value?</h3>
The vertical value in a pair of coordinates. How far up or down the point is. The Y Coordinate is always written second in an ordered pair of coordinates (x,y) such as (12,5). Also called "Ordinate".
Here, The "y-axis" is located on the "vertical axis" that represents the "dependent variable" (or, at times, the "control value") that cannot be "manipulated" / controlled/ or "selected" / since it represents the "y-value" of the corresponding coordinate to which the "x-value" happens to corresponds to at the given value for "x" .
Thus, the correct answer is: [A]: " Look at the graph of the relationship. Find the y-value of the point that corresponds to x = 1 . That value is the unit rate."
Learn more about Y-value from:
brainly.com/question/3319387
#SPJ1
Answer:
yes
Step-by-step explanation:
Having a dress code is very important for the workers because it makes it much easier to spot them and get the help you food. Plus it keeps the hair out of your food soooo-
++
Answer:
whats the question, and wheres the table ?
Step-by-step explanation:
Answer:
x = 9
y = 13
Step-by-step explanation:
Side-Side-Side or SSS means that if all three sides of one triangle are equal to all three corresponding sides of another triangle, then the two triangles are considered to be congruent (equal).
Therefore, GH = PM ⇒ 7x + 8 = 6y - 7
and, GP = HM ⇒ 8x - 10 = 5y - 3
Rewrite the first expression to make x the subject, then substitute this into the second equation, and solve for y:
GH = PM
⇒ 7x + 8 = 6y - 7
⇒ 7x = 6y - 15
⇒ x = (6/7)y - 15/7
Substituting x = (6/7)y - 15/7 into GP = HM:
GP = HM
⇒ 8x - 10 = 5y - 3
⇒ 8[(6/7)y - 15/7] - 10 = 5y - 3
⇒ (48/7)y - 120/7 - 10 = 5y - 3
⇒ (13/7)y = 169/7
⇒ y = 13
Now we have found a value for y, substitute this into one of the expressions and solve for x:
8x - 10 = 5y - 3
⇒ 8x - 10 = (5 x 13) - 3
⇒ 8x - 10 = 62
⇒ 8x = 72
⇒ x = 9